A Study on Marketing Strategies For Primary Healthcare Services In Chengalpattu District - Malathy, M. (Journal of Neonatal Surgery, 2025)
Marketing plays a crucial role in enhancing the reach and effectiveness of primary healthcare services. This study examines the impact of marketing strategies, particularly social media marketing, on promoting primary healthcare services in Chengalpattu District. Data analysis was conducted using various statistical tools, including Chi-Square tests, One-Way ANOVA, and Weighted Average Method (WAM), to assess the relationship between marketing channels and patient engagement. The findings reveal that most respondents (63%) strongly agree that social media marketing is a significant factor in promoting healthcare services. Statistical analysis also indicates a strong association between marketing channels and patient engagement, as well as the effectiveness of marketing efforts in improving healthcare communication. Furthermore, it was observed that healthcare marketing strategies vary based on factors such as patient demographics, communication frequency, and emerging technologies like AI and chatbots. The study highlights key marketing trends and provides recommendations for improving healthcare promotion, including integrating digital marketing, community outreach programs, and enhanced patient engagement techniques. By adopting innovative marketing strategies, primary healthcare providers can improve accessibility, awareness, and service utilization, ultimately contributing to better public health outcomes in Chengalpattu District.